Composition and «pointless» painting in system of nonconventional approaches to creative process - V.H. Shcherbyna; L.F. Eyvas (Освітній вимір, 2022)
In article the points of view on «pointless» painting as on one of aspects of abstract art and nonconventional approaches to creative process are analysed.